Resiliensi Pesantren Terhadap Ekstrimisme Kekerasan Berbasiskan Agama dan Implikasinya terhadap Masyarakat Pesisir Lamongan - Muthohirin, Nafik; Suherman, Suherman (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Pesantren has a strategy of resilience from the infiltration of the ideology of religious violent extremism. This resilience comes from the kiai's charisma and institutional commitment to the integrity of the country which has implications for the practice of Islamic education in Islamic boarding schools. This article discusses the form of the resilience of the Pesantren Karangasem Muhammadiyah Lamongan from the ideology of religious violent extremism. Pesantren Karangasem is located in Paciran, which borders Brondong, Lamongan, where religious life in the two coastal villages of Lamongan faces serious challenges because it is becoming pockets of movement for Islamic extremist groups. This article poses two thesis questions: First, what is the form of the resilience of the Pesantren Karangasem from the ideology of religious violent extremism; Second, how this form of resilience can have implications for preventing the entry of radical Islamic actors into the religious life of the coastal community of Lamongan. This study concludes that Pesantren Karangasem is an Islamic educational institution that contributes to spreading moderate Islamic views through several forms of resilience that originate from the kiai's charisma and the Islamic intellectual tradition of the pesantren. This study also emphasizes that even though the infiltration of massive religious-based violent extremism movements has occurred, the practice of Islamic cosmopolitan which is the character of religious life in the coastal community of Lamongan is always maintained.